O papel dos stakeholders na adoção de práticas de green supply chain management: estudo de caso em uma cadeia de suprimentos do setor de baterias automotivas - Seles, Bruno Michel Roman Pais [UNESP] (2015)
This research aimed to analyze how primary stakeholders of a focal company in a supply chain of the automative battery industry, influence the adoption of green supply chain management practices (GSCM). The method of case study research was adopted. The research helped identify the role of primary stakeholders in the adoption of a focal company's GSCM practices of a supply chain of the automotive battery industry. It was possible to identify that stakeholders and government customers exert environmental pressures on the focal company and that this influences the adoption of some GSCM practices. Environmental pressures have mainly received his client stakeholder, make the focal company manages a group of pressures, similar to those performed by your client on thier main supplier. This pressure also causes the focal company provider also adopt GSCM practices. The spread of environmental pressure was also identified and explained by the institutional environment isomorphism, the characteristics of automotive batteries industry and also the green bullwhip effect phenomenon